A review of the methodological characteristics of vocabulary interventions for emergent bilinguals in preschool to sixth grade. Issue 1 (31st January 2023) - Bengochea, Alain; Sembiante, Sabrina F.
Abstract: Vocabulary is foundational for reading and strongly linked to emergent bilingual (EB) students' academic achievement. Given the few syntheses on vocabulary interventions that are focused on emergent bilinguals, this literature review appraises the existing research and thoroughly accounts for methodological characteristics across studies relating to sample, treatment, and outcomes. We further investigate vocabulary teaching approaches that elicit positive vocabulary outcomes for preschool through to sixth grade EBs. Relevant intervention studies were identified and analysed for the study's sample, measure, and treatment characteristics as well as significant intervention outcomes. Analyses reveal that for sample characteristics there was a large amount of non‐reported information and a predominance of homogeneous, Spanish‐speaking, low second language proficiency sampling. For measurement characteristics, studies emphasised decontextualised and breadth of vocabulary knowledge as well as receptive vocabulary knowledge through oral responses. Patterns in treatment characteristics showed a prominence of unaligned treatment conditions, few investigations of home language support on EBs' vocabulary outcomes, and effectiveness of balanced approaches. Future research should build on effective balanced approaches and explore closer aligned comparison conditions with greater use of EBs' home languages. Practitioners should provide holistic vocabulary instruction for EBs that incorporates home language support, multimedia support during reading, and independent reading, all of which should provide extended and repeated vocabulary exposure.